2010
DOI: 10.1097/fjc.0b013e3181daded3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Direct Factor Xa Inhibitor Apixaban in Rat Models of Thrombosis and Hemostasis

Abstract: Apixaban is an oral, direct, and highly selective factor Xa inhibitor in late-stage clinical development for the prevention and treatment of thromboembolic diseases. Apixaban was evaluated in rat thrombosis and hemostasis models. Thrombosis was produced in the carotid artery by FeCl2 application, in the vena cava by either FeCl2 application or tissue factor injection, and in an arterial-venous shunt. Hemostasis was assessed using cuticle, renal cortex, and mesenteric artery bleeding times. Intravenous apixaban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…On the basis of the calculation from concentrations reported in literature, we found that >50% inhibition of thrombosis was observed at >97% fXa EO in a venous and arterial FeCl 2 thrombosis model and at >99% fXa EO in stasis and AVS thrombosis models in the rat, thus validating the choice of the model and animal species (Schumacher et al. 2010). These levels were consistent with the 99.2% calculated EO achieved at apixaban median C min (107 ng/mL) at the 5 mg BID SPAF dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of the calculation from concentrations reported in literature, we found that >50% inhibition of thrombosis was observed at >97% fXa EO in a venous and arterial FeCl 2 thrombosis model and at >99% fXa EO in stasis and AVS thrombosis models in the rat, thus validating the choice of the model and animal species (Schumacher et al. 2010). These levels were consistent with the 99.2% calculated EO achieved at apixaban median C min (107 ng/mL) at the 5 mg BID SPAF dose.…”
Section: Discussionmentioning
confidence: 99%
“…2009; Schumacher et al. 2010). It should be noted, however, that the apixaban doses, their pharmacodynamic effects (e.g., PT), and their antithrombotic activities were directly in agreement with published literature (Schumacher et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the translational relevance, it has to be mentioned that both similarities and differences exist between human and rodent coagulation systems. 31 Unfortunately, due to its long-term design, important pathophysiological measures could not be determined in this study. In particular, brain water content measurements are frequently performed in the context of experimental ICH.…”
Section: Apixaban Warfarinmentioning
confidence: 99%